A comparison of control strategies for the switchable damper suspension system. (4th August 2014) - Soliman, A.M.A.; Crolla, D.A.; El–Sayed, F.M.
Theoretical comparisons of control strategies for the switchable damper suspension system are made. Practical limitations involving switching time delays and threshold delay values are modelled and their effect on ride comfort quantified. The three–setting switchable damper is compared with the two–setting switchable damper. The effort of damper linearisation is studied. It is shown that the three–setting switchable damper offers worthwhile improvements over the passive and two–setting switchable damper.